Assessment Of Potential Clean Water Sources Meeting Criteria For Feasibility Study Of Establishing A Hospital In The Samarang Region Along The New Ibrahim Aji Road - Muhammad Nur Abdillah (Jurnal EduHealth, 2023)
This report assesses the water conditions and feasibility for both residents and hospitals in the Samarang area adjacent to the new road, Jl. Ibrahim Aji. The objective is to determine if the water conditions within the hospital comply with existing regulations. The research conducted for this report is of a descriptive nature. Based on the conducted interviews, it was revealed that the water supply in the vicinity of Jl. Ibrahim Aji is provided by a local water service, which, upon further investigation, draws its water from the Thunder Mountain springs. Organoleptic analysis suggests that this water is suitable for bathing, cooking, and other household needs. Regarding water sources used by hospitals, they utilize water from springs, rivers, lakes, and groundwater. However, it is imperative to ensure compliance with applicable standards. Based on the findings, it can be concluded that the groundwater in the area appears visually suitable for use, but further examination is required to assess its compliance with chemical, microbiological, and radiation safety criteria.